(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
This paper focus on the requiring of Made To Measure apparel production mode according to individual types and make calibration about body measurement and production in a line. In this paper, based on the measurement principle of structured light, a laser rotating body scanning of non-contact measurement system is introduced. Firstly, the key part of this system, such as digital motor, CCD, lens, etc, is introduced and discussed. Secondly, the principle of the whole system is brought up by analyzing the theory and realization of the structured light measurement, and a 3D reconstruction mathematical model is built based on the characteristic parameter of digital motor. Lastly, some important factors related to the accuracy of this system are discussed. The point cloud data of 3D body contour is acquired successfully via data processing and data piecing together. The further processing can be done according to the raw data. The validity of the principle of this system and the feasibility of arithmetic are veriby experiments.